SOSIALISASI DAN EDUKASI PEMBUATAN HAND SANITIZER BAHAN ALAMI BERUPA KEMANGI DAN LIDAH BUAYA DI LINGKUNGAN UNIVERSITAS PANCA MARGA - Renny Candradewi Puspitarini; Nurul Jannah Lailatul Fitria (Jurnal Abdi Insani, 2022)
Covid-19 is an infectious disease that can spread through objects and the air. People are advised to continue to maintain personal hygiene by washing their hands. If people are active outside their homes, washing their hands is a bit difficult because they have to find water and soap. The alternative to cleaning hands without water is replaced by the use of hand sanitizer. Currently in every place provided hand sanitizer. Including at Panca Marga University, paying attention to health protocols by providing the availability of hand sanitizers. This community service activity aims to socialize the manufacture of hand sanitizers with natural ingredients in the University environment to prevent the spread of the Covid-19 virus. Community service activities begin with observation. Then continued with a series of socialization and direct practice of making natural hand sanitizers. Service Activities Held in January 2022. The activity began with observations and requests for permission for activities to be carried out on the Panca Marga University. Furthermore, the activity was continued with socialization and the practice of making natural hand sanitizers. The results of natural hand sanitizer products are distributed to campus residents with the addition of flyers containing the procedures for making natural hand sanitizers. In addition, the distribution of natural hand sanitizers is also placed in every classroom at Panca Marga University to make it easier for campus residents to clean their hands when doing activities in class. So that this service is in accordance with the achievement target by implementing clean and healthy living behaviors in the campus environment during lecture activities. Socialization activities and distribution of natural hand sanitizers with basil and aloe vera made it easier for campus residents to clean their hands while on campus.